Effect of Hf and B incorporation on the SiOC precursor architecture and high-temperature oxidation behavior of SiHfBOC ceramics. Issue 2 (February 2020) - Lyu, Yang; Tang, Hui; Zhao, Guangdong
Highlights: A novel SiHfBOC polymer precursors and SiHfBOC ceramics were prepared. The ceramic yield of SiHfBOC ceramic is 85.8%. The t-HfO2 of SiHfBOC ceramics completely transformed into the m-HfO2 at 1300 °C. SiHfBOC ceramics have more excellent oxidation resistance and thermal stability than SiBOC ceramics. Abstract: Polymer-derived ceramics (PDCs), such as silicon oxycarbide and its derivatives, show an exceptional high oxidative stability under extreme conditions. A novel multicomponent silicon oxycarbide system tailoring with transition metal (hafnium) and boron is fabricated by sol-gel and solvothermal method. Amorphous SiHBOC was formed via the condensation of Si–OH, B–OH and Hf–OH groups, respectively, and the bonds of Si–O–Hf and Si–O–B– were detected by FTIR and XPS characterization. After high-temperature pyrolysis, the precursor is converted to a rigid ceramic material that has an 85.8 wt % ceramic yield of SiHfBOC. We investigate the oxidation resistance performance of SiHfBOC using the isothermal oxidation test at 1400 °C. The results showed that the oxidative stability of SiHfBOC was significantly superior to than those of SiBOC ceramic.